The New Canada Health Transfer: Increasing Disparity and Supporting Inertia? - Tsang, Adrian; Neves, Justin (The Meducator, 2012)
The current Canada Health Transfer which distributes 27 billion in cash and 13.6 billion in tax points to the provinces to support health care, will expire in 2014. Near the end of 2011, the Harper government surprised Canadians with a take-it-or-leave-it deal, whereby the Canada Health Transfer would be delivered with no-strings-attached and a decline in the rate of increased spending starting in 2017. The proposed deal reflects a growing hands off approach to healthcare in federal politics, furthers the divide between “have” and “have-not” provinces and represents a missed policy window for implementing significant healthcare reforms.